2017
DOI: 10.17944/mkutfd.376516
|View full text |Cite
|
Sign up to set email alerts
|

Şi̇zofreni̇ Ve Bi̇polar Bozukluklar İle Enfeksi̇yon Hastaliklari Arasindaki̇ İli̇şki̇ni̇n Araştirilmasi

Abstract: Considering the results of epidemiological studies, claimed that some congenital and postpartum infections in the intrauterine period, especially in 2nd Trimester, may play a role for the occurrence of Schizophrenia and Bipolar Disorder (BD). Aim of our study; serum samples of schizophreni-BD patients and healthy asymptomatic donors, Toxoplasma gondii (T.gondii), Chlamydia pneumoni (C.pneumoniae), Chlamydia trachomatis (C.trachomatis), Cytomegalovirus (CMV), Herpes simplex Virus(HSV1-HSV2), Treponema pallidum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Using epidemiology, immunology, and genomic tools helps to examine the biology of infectious diseases. Lots of research has been done on the epidemiology, immunology, and genomics of C. trachomatis [11,[18][19][20][21][22][23][24][25]. In this study, it was shown that the studies on C. trachomatis were mostly related to the disease in the fields of Infectious Diseases, Microbiology, and Immunology.…”
Section: Discussionmentioning
confidence: 99%
“…Using epidemiology, immunology, and genomic tools helps to examine the biology of infectious diseases. Lots of research has been done on the epidemiology, immunology, and genomics of C. trachomatis [11,[18][19][20][21][22][23][24][25]. In this study, it was shown that the studies on C. trachomatis were mostly related to the disease in the fields of Infectious Diseases, Microbiology, and Immunology.…”
Section: Discussionmentioning
confidence: 99%